Pengaruh Media Wordwall dalam Meningkatkan Minat Belajar Pendidikan Pancasila Siswa Kelas 5 SDN Balekambang 01 Pagi - Rudy Gunawan; Muhammad Fickry (EduInovasi: Journal of Basic Educational Studies, 2024)
The aim of this study is to ascertain how the use of Wordwall media by class V students at SDN Balekambang 01 Pagi affects their motivation to pursue Pancasila education. This is a quasi-experimental, quantitative study with a posttest-only control design. For the study, a sample of sixty fifth graders was used. They were divided into two groups: the experimental group used Wordwall, and the control group did not. A questionnaire is used to collect data on students' enthusiasm in learning. The results of the data analysis show that the grade 5 students at SDN Balekambang 01 Pagi's interest for learning about Pancasila Education is greatly impacted by their consumption of Wordwall media. The effect size test demonstrates a modest effect (0.494) and the t test results show that the t value is larger than the t table (2.158 > 2.002). These results provide empirical evidence that Wordwall is a useful tool for stimulating students' interest in Pancasila Education courses.